Validation of the somatic symptom disorder—B Criteria Scale (SSD-12) in Bangladesh - Sumaiya Habib; Muhammad Kamruzzaman Mozumder (PLoS ONE, 2025)
Background The absence of a reliable and valid Bangla instrument for measuring somatic symptom disorder hinders research and clinical activities in Bangladesh. The present study aimed at translating and validating the Somatic Symptom Disorder-B criteria (SSD-12). Method A cross-sectional design was used with purposively selected clinical (n = 100) and non-clinical (n = 100) samples. The clinical sample was collected from psychiatric departments at three hospitals, while the non-clinical sample was drawn from the local community. Exploratory (EFA) and confirmatory factor analysis (CFA) were conducted on the SSD-12, along with reliability and validity assessments. Results Results indicated satisfactory internal consistency reliability (Cronbach’s alpha = .94, split-half r = .93); criterion-related validity (r = .86, with Morey’s Somatic Complaints Scale); and construct validity (r = .64 with anxiety subscale and r = .57 with depression subscale of the Hospital Anxiety and Depression Scale) of the translated scale. In contrast to the three-factor structure of the original SSD-12, the Bangla version indicated a single-factor structure (accounting for 61.29% of the total variance). This scale also demonstrates its ability to distinguish between clinical and non-clinical participants (t198 = 16.74, p < .01). Conclusion The Bangla translated SSD-12 has demonstrated strong psychometric properties, indicating its suitability for use in Bangladesh. This tool is expected to aid mental health practitioners in their clinical work by providing them with a quick assessment of their patients having somatic complaints.